Diazotrophs: Overlooked Key Players within the Coral Symbiosis and Tropical Reef Ecosystems? - Benavides, Mar; Bednarz, Vanessa N.; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2017)
Coral reefs are highly productive ecosystems thriving in nutrient-poor waters. Their productivity depends largely on the availability of nitrogen, the proximate limiting nutrient for primary production. In reefs, the major nitrogen pathways include regeneration, nitrification, ammonification and dinitrogen (N2) fixation. N2 fixation is performed by prokaryotes called ‘diazotrophs’ that abound in coral rubbles, sandy bottoms, microbial mats or seagrass meadows. Corals, which are the main reef builders, have developed a partnership with dinoflagellates which transform dissolved inorganic nitrogen into amino acids and protein, and with diazotrophs to gain diazotrophically-derived nitrogen (DDN). Pioneering studies found active diazotrophic cyanobacteria in the corals’ mucus and/or tissue, and later high throughput sequencing efforts have described diverse communities of non-cyanobacterial diazotrophs associated with scleractinian corals. Yet, the metabolic processes behind these associations and how they benefit corals is currently not well understood. While genomic studies describe the diversity of diazotrophs and isotopic tracer experiments quantify N2 fixation rates, combined advanced methods are needed to elucidate the mechanisms behind the transfer of DDN to the coral holobiont and whether these mechanisms change according to the identity of the diazotrophs or coral species. Here we review our current knowledge on N2 fixation in corals: the diversity and localization of diazotrophs in the coral holobiont, the environmental factors controlling N2 fixation, the fate of DDN within the coral symbiosis as well as its potential role in coral resilience. We finally summarize the unknowns: are the diversity, abundance and localization of diazotrophs within the holobiont species- and/or site-specific? Do they have an impact on DDN production? What are the metabolic mechanisms implicated? Do they change spatially, temporally or according to environmental factors? We encourage scientists to undertake research efforts to tackle these questions in order to shed light on nitrogen cycling in reef ecosystems and to understand if coral-associated N2 fixation can improve coral’s resilience in the face of climate change.